Assessing complex PTSD and PTSD: validation of the German version of the International Trauma Interview (ITI) - Bachem, Rahel; Maercker, Andreas; Levin, Yafit; Köhler, Kai; Willmund, Gerd; Bohus, Martin; Koglin, Stefanie; Roepke, Stefan; Schoofs, Nikola; Priebe, Kathlen; Wülfing, Felix; Schmahl, Christian; et al. (European journal of psychotraumatology, 2024)
Background: With the introduction of the ICD-11 into clinical practice, the reliable distinction between Posttraumatic Stress Disorder (PTSD) and Complex Posttraumatic Stress Disorder (CPTSD) becomes paramount. The semi-structured clinician-administered International Trauma Interview (ITI) aims to close this gap in clinical and research settings. Objective: This study investigated the psychometric properties of the German version of the ITI among trauma-exposed clinical samples from Switzerland and Germany. Method: Participants were 143 civilian and 100 military participants, aged M = 40.3 years, of whom 53.5% were male. Indicators of reliability and validity (latent structure, internal reliability, inter-rater agreement, convergent and discriminant validity) were evaluated. Confirmatory factor analysis (CFA) and partial correlation analysis were conducted separately for civilian and military participants. Results: Prevalence of PTSD was 30% (civilian) and 33% (military) and prevalence of CPTSD was 53% (civilians) and 21% (military). Satisfactory internal consistency and inter-rater agreement were found. In the military sample, a parsimonious first-order six-factor model was preferred over a second-order two-factor CFA model of ITI PTSD and Disturbances in Self-Organization (DSO). Model fit was excellent among military participants but no solution was supported among civilian participants. Overall, convergent validity was supported by positive correlations of ITI PTSD and DSO with DSM-5 PTSD. Discriminant validity for PTSD symptoms was confirmed among civilians but low in the military sample. Conclusions: The German ITI has shown potential as a clinician-administered diagnostic tool for assessing ICD-11 PTSD and CPTSD in primary care. However, further exploration of its latent structure and discriminant validity are indicated. This study validated the German International Trauma Interview (ITI), a semi-structured clinician-administered diagnostic interview for ICD-11 Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder.Internal reliability, inter-rater agreement, latent structure, and convergent validity were explored in trauma-exposed clinical and military samples from five different in- and outpatient centres in Germany and German-speaking Switzerland.The findings supported the German ITI's reliability, inter-rater agreement, convergent validity and usefulness from a patient perspective. Future research should explore its factor structure and discriminant validity, for which differences between the samples were found. This study validated the German International Trauma Interview (ITI), a semi-structured clinician-administered diagnostic interview for ICD-11 Posttraumatic Stress Disorder and Complex Posttraumatic Stress Disorder. Internal reliability, inter-rater agreement, latent structure, and convergent validity were explored in trauma-exposed clinical and military samples from five different in- and outpatient centres in Germany and German-speaking Switzerland. The findings supported the German ITI's reliability, inter-rater agreement, convergent validity and usefulness from a patient perspective. Future research should explore its factor structure and discriminant validity, for which differences between the samples were found.
Gesehen am 10.03.2025